Deskripsi Tingkat Kesejahteraan Masyarakat Nelayan - Mardalena; Sitti Kasmiati; La Ode Nursalam (Jurnal Penelitian Pendidikan Geografi, 2022)
Lakara Village is an area where the majority of the population work as fishermen where their income is influenced by internal factors and external factors. The purposes of this study are: 1) to analyze the level of welfare of the fishing community in Lakara Village, Palangga Selatan District; and 2) to describe the economic conditions of the fishing community in Lakara Village, Palangga Selatan District. This type of research is a qualitative descriptive study with a total of 26 respondents. The data in this study were collected through observation, interviews, questionnaires and documentation studies. The results showed that: 1) 23% of fishing families had not been able to reach a prosperous family level, followed by 11.5% of KS I, 23% of KS II, 30.7% of KS III, and 11.5% of KS III+ %; and 2) the economic condition of the fishing community in Lakara Village, in terms of income and expenditure, varies from Rp. 1,500,000 to Rp. 4,000,000. The fishing community of Lakara Village is in the high category, namely Rp. 3,000,000- Rp. 3,500,000 for 11 respondents or the equivalent of 42.3%, while the expenditure of the fishing community in Lakara Village is in the medium category, namely Rp. 2,000,000 – Rp. 2,500,000 as many as 11 people or 42.3%.